Determinan Performance of the Government of North Sulawesi Province - Frida Magda Sumual (AIBPM Publisher, 2018)
According to PP No. 58 of 2005 concerning regional financial management explained that performance is the output or outcome of an activity or program that has been or will be achieved by using a budget with measurable quantity and quality. Local governments have a responsibility to achieve good governance reflected in the performance of local governments. The government is categorized as having good performance, if it is able to manage the government so that it can provide welfare to the community as a whole. There are several factors that influence the performance of a region's government, including: public participation, internal control systems, transparency in regional financial management, public accountability, and the quality of financial statements. The performance of the financial statements of the North Sulawesi provincial government in 2016 which was assessed by the Supreme Audit Agency (BPK-RI) was unqualified (WTP). The conformity of the financial report preparation standards made by the North Sulawesi Provincial Government which was assessed by the BPK-RI, has not yet been followed by the implementation of Government Institutional Performance Accountability (AKIP) that is in accordance with the standards assessed by the Ministry of Administrative Reform, and also with compliance with Public Service Standards. which was assessed by the Indonesian Ombudsman. The finding of a discrepancy between the predicate of unqualified opinion (WTP), with the implementation of Government Institutional Performance Accountability (AKIP) that is not yet compliant with standards, and not fulfilling compliance in fulfilling public service standards raises an interesting problem to examine as a research problem. The purpose of this study is to examine the performance of local government and the phenomena revealed, the factors that influence it, and the interaction of influence between these factors, both direct (direct effect) and indirect (indirect effect). Keywords: Local Government Performance